Comparative Study Between Ultrasound And KUB And IVU In Renal Colic Patiens In Kelantan - Ismail, Harith Sherifuddin (2001)
Intravenous urography has been a standard investigative method in patients with nephrolithiasis. Routine use of intravenous urography has shown to increase examination time and cost. Besides, it requires ionizing radiation and contrast media that carries a risk to the patient. Ultrasound can detect calculi and dilatation of the pelvicalyceal system. Combination of KUB and US can significantly improve the detection of calculi especially at the ureter. The study illustrates the effectiveness of ultrasound and KUB in evaluating renal colic patients compared to IVU.